2011
DOI: 10.1016/j.chemosphere.2010.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive two-dimensional gas chromatography time of flight mass spectrometry (GC×GC-TOFMS) for environmental forensic investigations in developing countries

Abstract: a b s t r a c tThe disposal and dumping of toxic waste is a matter of growing concern in developing countries, including South Africa. Frequently these countries do not possess access to gas chromatography-high resolution mass spectrometry (GC-HRMS) for the determination of persistent organic pollutants (POPs). This publication describes an alternative approach to the investigation of toxic waste using comprehensive gas chromatography coupled to time of flight mass spectrometry (GC Â GC-TOFMS). The technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Panić and Górecki reviewed GC×GC in environmental analyses and monitoring and they indicated that the main challenge in environmental analysis is that the analytes are usually present in trace amounts in very complex matrices (Panić & Górecki, 2006). In overcoming this problem, GC×GC-MS is a very powerful and attractive system that has been successfully applied for powerful identification of polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) (de Vos et al, 2011), polychlorinated biphenyls (PCBs) (Focant et al, 2004;Hoh et al, 2007), polychlorinated naphthalenes (PCNs) (Korytár et al, 2005), nonyl phenol (NP) (Eganhouse, et al, 2009), benzothiazoles, benzotriazoles, benzosulfonamides (Jover et al, 2009), Cl-/Br-PAH congeners (Ieda et al, 2011), pharmaceuticals and pesticides (Matamoros et al, 2010) in complex environmental samples.…”
Section: Novel Gc Techniquesmentioning
confidence: 99%
“…Panić and Górecki reviewed GC×GC in environmental analyses and monitoring and they indicated that the main challenge in environmental analysis is that the analytes are usually present in trace amounts in very complex matrices (Panić & Górecki, 2006). In overcoming this problem, GC×GC-MS is a very powerful and attractive system that has been successfully applied for powerful identification of polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) (de Vos et al, 2011), polychlorinated biphenyls (PCBs) (Focant et al, 2004;Hoh et al, 2007), polychlorinated naphthalenes (PCNs) (Korytár et al, 2005), nonyl phenol (NP) (Eganhouse, et al, 2009), benzothiazoles, benzotriazoles, benzosulfonamides (Jover et al, 2009), Cl-/Br-PAH congeners (Ieda et al, 2011), pharmaceuticals and pesticides (Matamoros et al, 2010) in complex environmental samples.…”
Section: Novel Gc Techniquesmentioning
confidence: 99%
“…The National Metrology Institute of South Africa (NMISA), in collaboration with various institutions, launched the project towards a comprehensive screening method for multiple classes of persistent organic pollutants (POPs) in one run using Comprehensive Gas Chromatography-Time-of-Flight Mass Spectrometry (GC×GC-TOFMS) [5,6]. There are numerous challenges that have to be overcome with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the selectivity lost due to low resolution mass spectrometry (vs HRMS) will be offset by the higher selectivity of the extra gas chromatographic dimension. Moreover, as full range mass spectral data are always acquired (detailed full range mass spectral acquisition for selected classes of POPs is described in a previous paper [6]), it is not a target compound technique such as single ion monitoring (SIM), and is ideal for screening for multiple classes of environmental pollutants in a single analysis [1,[10][11][12][13][14]. Retrospective data mining of archived data will be possible when future focus turns to new target compounds, e.g., the brominated dioxins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods not only screen for a variety of potentially harmful compounds, but can also accurately quantify POPs at the concentrations required by statutory organizations in first world countries (9,10,11). Such methodologies must be affordable, simple and robust, because in addition to limited funding, in many developing countries there is also a shortage of qualified personnel that can routinely conduct these analyses.…”
mentioning
confidence: 99%